Is antifungal resistance a cause for treatment failure in dermatophytosis: A study focused on tinea corporis and cruris from a tertiary centre? - Kabir Sardana; Ravinder Kaur; Pooja Arora; Ritu Goyal; Sneha Ghunawat (Wolters Kluwer Medknow Publications, 2018)
Background: Dermatophytoses are one of the most common skin diseases that have been largely simple to treat. However, in recent years, these infections have become recalcitrant to treatment which can possibly be due to antifungal resistance. Aim: To analyze the resistance pattern of patients with recalcitrant dermatophytoses. Materials and Methods: A cross-sectional evaluation was undertaken of 40 consecutive patients with recalcitrant tinea corporis/cruris/both who had taken systemic antifungal treatment and did not respond completely to therapy or had recurrent lesion within 1 month of stopping the therapy. Terbinafine, fluconazole, itraconazole, ketoconazole, amphotericin B, and voriconazole were the antifungals tested using broth microdilution assay for antifungal susceptibility testing of dermatophytes, and MIC50, 90 values were recorded. Results: KOH mount was positive in 18 (45%) patients, culture was positive in 28 (70%) patients. Trichophyton mentagrophytes (35%) and T. rubrum (27.5%) were the predominant isolates. Overall, activity of terbinafine and itraconazole were significantly higher than the other drugs tested. For terbinafine, both T. mentagrophytes and T. rubrum were inhibited at MIC90of 0.125 μg/ml. Itraconazole-inhibited T. mentagrophytes and T. rubrum at MIC90of 0.0625 and 0.25 μg/ml, respectively. All isolates had reduced susceptibility to fluconazole. Conclusion: While MIC seen were higher than western data, in-vitro resistance (>1 μg/ml) to antifungals was not seen and probably may not be a cause of treatment failure. Possibly, treatment failure lies in the intricate host fungal interaction and virulence of species which help it to evade host immune response.